2015
DOI: 10.1007/s00011-015-0831-z
|View full text |Cite
|
Sign up to set email alerts
|

Cafeteria diet-fed mice is a pertinent model of obesity-induced organ damage: a potential role of inflammation

Abstract: Functional and structural damage in CAF were higher than HF of similar macronutrient composition. This study provides a novel dietary model in mice that mimics multi-organ physiologic alterations in humans secondary to obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
2
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 42 publications
7
49
2
10
Order By: Relevance
“…Brunetti et al 28 and Zeeni et al 2 used the CAF diet as a model of induced obesity in mice and found MUFA values of 77.27 and 55%, respectively, similar to our results.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Brunetti et al 28 and Zeeni et al 2 used the CAF diet as a model of induced obesity in mice and found MUFA values of 77.27 and 55%, respectively, similar to our results.…”
Section: Resultssupporting
confidence: 91%
“…The CAF diet presented higher total lipid (32.36 ± 4.77%) and energy (539.34 ± 23.99%) values than the ST diet, due to the addition of peanut, chocolate and biscuit in its preparation, foodstuffs with high fat/energy. 22,23 It was observed that the CAF diet presented a higher proportion of fat in its composition when compared to the ST diet; this was also observed in studies conducted by Zeeni et al, 2 Suárez-García et al 24 and Cardoso et al 25 In our study, peanut, chocolate and biscuit were used to increase the caloric density of the CAF diet; other studies used bacon, 10 sweet roll 24 and peanut butter. 2 Although the basis of all CAF diets is high fat and calories, their composition is very different, not having a standard regarding the amount and composition of the food.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations